Detection of Listeria monocytogenes in Several Types of Frozen Meat in Baghdad city - Safana A. S. Yassin,; Ban N. Nadhom ,; Nagham M. Al-Gburi, (Iraqi Journal of Science, 2021)
Detection of pathogenic bacteria, such as Listeria monocytogenes, in food is crucial for safeguarding public health in Iraq. Forty five samples of frozen meat (15 samples of each of minced red meat, chicken, and fish) were collected from different markets in Baghdad city. Molecular (RT-PCR) and culturing (conventional microbiological examination) methods were used to determine the level of contamination of L. monocytogenes in these types of meat.For the culturing method, TSYEB broth was used as an enrichment medium, whereas BALCAM medium (HiMedia) with the listeria selective supplement FD061 was used as a selective medium, for the isolation and identification of this bacterium. The isolates were confirmed microscopically and biochemically. The results of the culturing method showed that the total number of the isolates of L. monocytogenes was 14/45 (31.1%). The incidence of this bacterium was high in fish (11/15, 73.3%), while it was low in the other two types of meat. 2/15 (13.3%) in red meat and 1/15 (6.7 %) in chicken.Molecular detection of each sample of the bacteria was performed using RT-PCR technique after preparing the Genomic DNA extraction of these samples according to the protocol provided by ReliaPrep™ Blood gDNA Miniprep System kit (Promega, USA). The PCR primers and the hybridization probe ((Macrogen, Korea) were used to target the inlA gene sequence (specific for L. monocytogenes). The results of the RT-PCR assay showed that 10/45 (22.2%) of the samples were positive for L. monocytogenes, which was detected only in fish samples ((10/15, 66.7%), while not found in minced red meat and chicken. However, our results showed differences when compared to other previous works because there were many studies found that the highest contamination rate was in red meat products.We conclude that the PCR kit used for the detection of L monocytogenes appears to give accurate results in the diagnoses of this bacterium in meat products and in comparison with the other routine diagnosis methods in the laboratory, which included culturing and doing biochemical tests which last for approximately 7 days, the RT-PCR technique was able to confirm the findings within 48 hours.